2000
DOI: 10.1007/s004010000216
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of myotonic dystrophy protein kinase in brain and its relevance to clinical phenotype

Abstract: To investigate the pathophysiologic role of myotonic dystrophy protein kinase (DMPK) in the brain in myotonic dystrophy (MD), the developmental characteristics of DMPK immunoreactivity in the central nervous system and its alteration with disease were studied. Eleven patients' brain with MD (5 congenital form, 6 adult form) were examined by immunohistochemistry using a specific antibody against synthetic DMPK peptides, antipeptide DM1, and compared with 30 control brains, including 16 age-matched controls. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Previous neuroimaging studies have demonstrated predominant white matter abnormalities rather than cortical changes in the brain. Symmetrical subcortical white matter lesions with a breakdown of myelin sheaths and relative preservation of axons in patients with DM1 are the most common previously reported pathological marker 1819. Group comparison between patients and control subjects in this study revealed higher occurrence of white matter abnormalities than cortical abnormalities, which was in line with previous reports 1820.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous neuroimaging studies have demonstrated predominant white matter abnormalities rather than cortical changes in the brain. Symmetrical subcortical white matter lesions with a breakdown of myelin sheaths and relative preservation of axons in patients with DM1 are the most common previously reported pathological marker 1819. Group comparison between patients and control subjects in this study revealed higher occurrence of white matter abnormalities than cortical abnormalities, which was in line with previous reports 1820.…”
Section: Discussionsupporting
confidence: 91%
“…Detailed analyses of white matter microstructure using DTI showed that white matter lesions mostly represent myelinopathy, as areas of change in mean diffusivity values were mostly influenced by RD values, except corpus callosal changes in AD. This finding together with the correlation between white matter lesion severity and disease duration suggests that DM1 represents a slow demyelinating process 1820. The demyelination eventually progresses to axonopathy, leading to ventricular dilatation, which is significantly more common in patients with severely disturbed intellect 2.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, IQ declines as the age of DM1 onset decreases and the CTG expansions increases [36,38,39]; although, IQ apparently does not correlate with the neuromuscular impairment. The cognitive defects are supported by neuropathological findings and neuroimaging: (1) reduced cerebral perfusion in the frontal and temporal lobes by H 2 O PET scan correlated with cognitive impairment [40]; (2) a variety of abnormalities were discovered such as neurofibrillary tangles, intracytoplasmic inclusions and subcortical white matter lesions with a breakdown of myelin sheets, with relative preservation of axons and the presence of fatty granular cells [41][42][43]. No imaging study is currently available in patients with the juvenile form of DM1.…”
Section: Discussionmentioning
confidence: 93%
“…The specific cognitive defects in the myotonic patients are supported by neuropathological findings that include a variety of abnormalities, the most common of which are neurofibrillary tangles, intracytoplasmic inclusions, subcortical white matter lesions with a breakdown of myelin sheets, and relative preservation of axons, and the presence of fatty granular cells 50, 51, 61, 219, 227. The tendency toward symmetry and confluence of the white‐matter lesions, progressive ventricular enlargement, and correlation between white‐matter lesion severity and disease duration suggest a slow demyelinating process 51, 196.…”
Section: Myotonic Dystrophy (Steinert Disease)mentioning
confidence: 94%